Synthesis, characterization and photophysical properties of mixed ligand cyclometalated platinum(II) complexes containing 2-phenylpyridine and pyridine carboxylic acids. (1st February 2023) - Sifnaiou, Evangelia; Garypidou, Antonia; Ypsilantis, Konstantinos; Plakatouras, John C.; Garoufis, Achilleas
Graphical abstract: Mixed ligand cycloplatinates with 2-phenylpyridine and pyridine carboxylic acids were synthesized and characterized both in acetone solutions and solid state. The solution-structural features of the complexes were identified by NMR spectroscopic techniques. The complexes were examined for their luminescence. All complexes in acetone solution have a very low emission quantum yield, while in solid state this yield was increased, because of the inter-ligand aromatic stacking. Highlights: Cycloplatinated complexes with 2-phenylpyridine and pyridine carboxylic acids were synthesized. The X-ray structure of the synthesized complexes were determined. The solution features of the complexes were identified by NMR spectroscopic techniques. Cycloplatinates were examined for their luminescence in solution and solid state. Abstract: Cyclometalated mixed ligand platinum(II) complexes containing 2-phenylpyridine (ppyH) and pyridine carboxylic acids (PCAs), namely picolinic (2-pyacH), nicotinic (3-pyacH) and isonicotinic (4-pyacH) acid, with the general formula trans -N, N-[Pt(ppy)(PCA)Cl] [PCA = 2-pyacH (2 ), 3-pyacH (3 ), 4-pyacH (4 )] were synthesized and characterized. The crystal structures of the complexes 3 and 4 showed that the PCAs coordinated in a trans- position towards the orthometalated ppyC, forming hydrogen-bonded homodimers through their carboxylic groups. NMR spectroscopic techniques were used to identify the solution-structural features of the complexes 2 –4 . The results revealed that the dihedral angle ( γ ) between the PCA plane and the plane of ppy depends on the carboxylic substitution of the pyridine ring and, in the cases of 3 and 4, the solid-state characteristics were retained. All complexes emit similarly in degassed solution of acetone (475–580 nm) with a very low quantum yield ( Φ  ∼ 0.05–0.17 %), while in the solid state, a green emission centered at about 530 nm with Φ varying from 3.20–4.86 % is produced.